DEVELOPMENT OF SPIRITUALITY ASSESSMENT OF NURSING INSTRUMENTS IN NURSES AT LABUANG BAJI HOSPITAL MAKASSAR - Patima -; Syamsuddin AB (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Spiritual care is carried out by nurses for patients, to prevent more severe health effects and warn of their illness, besides fulfilling spiritual needs that are holistic care to improve patient rehabilitation and quality of life when patients are treated. The aim of the study was to find out the development of an instrument for assessing the spiritual aspects of patients. This research is a qualitative research, the researcher synthesizes and constructs an instrument for assessing the patient's spiritual aspects, while the informants are five expert nurses, nursing practitioners and experts in the field of nursing science specifying spiritual aspects. The stages of the instrument development process are the construction stage, the preparation of the grid, the development of variable dimensions and indicators, theoretical and empirical validation, expert panels and review revisions based on input from the expert panel. The results show that after carrying out the instrument development process, this research has found five dimensions of spiritual aspects assessment, namely: the dimensions of spiritual experience, positive emotions, the meaning of life, rituals (for non-Muslims) and rituals (for Muslims). While discussing spiritual experience is a manifestation of spirituality within a person in the form of specific and unique experiences related to his relationship with God at various levels, one's spirituality is related to the purpose and meaning of life as a whole as a manifestation of his relationship with God, spirituality has four dimensions, namely the meaning of life, positive emotions, spiritual experiences, and rituals